Factors Affecting Tomato Production in Batu City, Indonesia - Besi, Yuliana Dewilda; Asnah, Asnah; Dyanasari, Dyanasari (Agro Bali : Agricultural Journal, 2025)
The high market demand for tomatoes means farmers play an essential role in increasing production. Some factors can influence plant productivity, impacting demand and the amount of tomato production. The research aims to determine the factors influencing tomato production and the efficiency of using production factors in Batu District, Batu City. The research was carried out in Batu District, Batu City, East Java, in March 2024, with the number of samples in this research being 80 farmers, and samples were taken from 15 farmer groups. The data analysis method used in this research to determine the influence of tomato farming production factors (land area, seeds, fertilizer, labor and pesticides) is the Cobb-Douglas model analysis and technical, allocative and economic efficiency. The results of the research show that The factors that influence tomato production in Sumberejo Village, Batu District, Batu City, namely the land area variable (X1), the seed variable (X2), and the manure variable (X3) have a partial significant positive effect on tomato production results. In contrast, the labor variable ( X7) partially has a negative effect on tomato production, with the technical efficiency of variables X1, X2, X3, X4, X5, X6 and Meanwhile, Variable allocative efficiency X1, X2, X4, X6, and X7 allocatively (NPMx / Px) < 1 inefficient use of input, Meanwhile variables X3 and X5 allocatively (NPMx / Px) > 1 Inefficient use of input, Variable economic efficiency X1, X2, X3, X4, X6, and X7 economically (EE = <1) inefficient while variables X5 economically (EE = >1). it is not yet efficient. The contribution of this research to science or the surrounding community is as an internal reference for business development and increasing the added value of agricultural products as well as increasing knowledge and understanding also broadens insight into the efficient use of production factors in farming.